In utero Exposure to Excessive Estrogen Impairs Homologous Recombination and Oogenesis via Estrogen Receptor 2 in Mice - Mu, Xinyi; Tu, Zhihan; Chen, Xuemei; Hong, Yi; Geng, Yanqing; Zhang, Yan; Ji, Xingduo; Liu, Taihang; Wang, Yingxiong; He, Junlin (Frontiers in Cell and Developmental Biology, 2021)
The association between the accumulation of synthetic chemicals with estrogenic activity and risks to oogenesis has become a growing concern. This study indicates that in utero estrogen exposure can affect homologous recombination in early oogenesis and influence the reproductive potential and lifespan of female offspring. We conducted this study in developing mouse ovaries using two different models: oral doses administered to the mother, and fetal ovary cultures. Our analyses of meiotic fetal oocytes suggest that 17-β-estradiol induces gross aberrations in prophase I events, including delayed meiotic progression, increased unrepaired DNA damage, and altered homologous recombination levels. These effects were mainly mediated by estrogen receptor 2 (ESR2) activation. Mid-gestation exposure to estrogen also led to delayed primordial folliculogenesis after birth, impaired follicle development after prepuberty, and ultimately reduced the total litter size of the offspring. This raises the concern that maternal exposures to substances activating ESR2 may compromise the fertility of the exposed female fetus.